1997
DOI: 10.1056/nejm199708143370704
|View full text |Cite
|
Sign up to set email alerts
|

Clonality in Nodular Lymphocyte-Predominant Hodgkin's Disease

Abstract: Clonal populations of L&H cells occur in nodular lymphocyte-predominant Hodgkin's disease. Intraclonal variation in nucleotide sequences suggests that hypermutation of the heavy-chain CDR3 continues to occur among the clonal progeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
7

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(63 citation statements)
references
References 25 publications
3
52
1
7
Order By: Relevance
“…1,2,26,27,[32][33][34] In LPHD, a single clone of lymphocytic and histiocytic cells, characterized as the descendant of a centroblast, is found in the different nodules of the lymphoma. 10,16,17 Although the detection of single clones of Ki67 ϩ cells encompassing 50% to 70% of the mutated Ki67 ϩ cells in 3 PTGCs may be suggestive of aberrant clonal expansions, such expansions are not unusual for classical GCs. 14,28,30,35 To address the question whether PTGCs might represent preneoplastic lesions, we analyzed in each of 2 patients the Ki67 ϩ cells from 2 different PTGCs.…”
Section: Relation Of Ptgcs To Lphdmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,26,27,[32][33][34] In LPHD, a single clone of lymphocytic and histiocytic cells, characterized as the descendant of a centroblast, is found in the different nodules of the lymphoma. 10,16,17 Although the detection of single clones of Ki67 ϩ cells encompassing 50% to 70% of the mutated Ki67 ϩ cells in 3 PTGCs may be suggestive of aberrant clonal expansions, such expansions are not unusual for classical GCs. 14,28,30,35 To address the question whether PTGCs might represent preneoplastic lesions, we analyzed in each of 2 patients the Ki67 ϩ cells from 2 different PTGCs.…”
Section: Relation Of Ptgcs To Lphdmentioning
confidence: 99%
“…10,16,17 Consequently, to study the relation between LPHD and PTGCs, we analyzed, from each of 2 lymph nodes, Ki67 ϩ cells from 2 individual PTGCs for clonal expansion across the borders of individual PTGCs.…”
Section: Micromanipulation and Single-cell Analysismentioning
confidence: 99%
“…[27][28][29] In addition rearrangements of BCL6 were detected by fluorescence in situ hybridization in about 48% of cases, further supporting a relationship with germinal center B cells. 30 By combining comparative genomic hybridization and microdissection of single neoplastic cells with subsequent DNA amplification by degenerate oligonucleotide-primed polymerase chain reaction (DOP-PCR), Franke et al demonstrated the presence of frequent genomic imbalances in lymphocyte-predominant cells.…”
Section: Genetics and Gene Expression Profilingmentioning
confidence: 80%
“…Many different techniques have been used to provide evidence to support a probable derivation of RS cells from either B-lymphocytes (24, 25), T lymphocytes (32, 33), and dendritic cells (34 -36). The neoplastic cells in lymphocyte predominant Hodgkin lymphoma originate from a B-lymphocyte, a suggestion confirmed by single cell polymerase chain reaction (PCR) studies (37,38). Germinal center B cells have been proposed as the normal counterpart of L&H variants, as supported by the presence of somatic hypermutation of the immunoglobulin genes and BCL-6 expression (37,39).…”
Section: Discussionmentioning
confidence: 96%